Fatores epidemiológicos e clínicos associados a incoagulabilidade sangüínea no envenenamento por serpentes do gênero Bothrops - Oliveira, Ricardo Borges de (1999)
In Brazil, approximately 90% of snake accidents are caused by snakes of the Bothrops genus, which cause poisoning with a lethality of 0.3%. Although the change in coagulation is the most frequent systemic manifestation in these accidents and occurs early, it does not seem to have a good association with the degree of poisoning in the bitten anatomical region. This led to 'its removal from the criteria for classification as to' the severity of the poisoning, with the aim of administering an adequate dose of serum. On the other hand, some authors have found an association between coagulopathy and progression to necrosis, abscess and death. The present study aims to know, in poisoning by snakes of the Bothorps genus, epidemiological and clinical factors that may be associated 'with blood incoagulability and to verify if this alteration is associated' with the clinical evolution of patients. Information on epidemiological, clinical and laboratory variables related to poisonings was obtained from 2,991 medical records of patients bitten by snakes of the Bothrops genus, seen at the Vital Brazil Hospital of the Butantan Institute (HVB-IB), from 1981 to 1990. Patients were grouped between those who did not show blood incoagulability (Group 1) and those who did show such change (Group 2). The following variables were positively associated with blood incoagulability (p <0.05): occurrence of accidents in the last months of the year; stings in distal segments of the lower limbs; presence of pain, edema and ecchymosis in the pricked anatomical region; occurrence of systemic bleeding and shock; dose of polyspecific serum administered; time between accident and arrival at the HVB. Associated2 negatively 'blood incoagulability (p <0.05): size of snake B. jararaca', use of tourniquet; time between arrival at HVB and start of serotherapy. Blood incoagulability was not associated (p> 0.05): time of the accident; presence of freshly swallowed prey in the snake's digestive tract; patient's gender and age; presence of a blister, necrosis and abscess in the pricked anatomical region; occurrence of amputation, renal failure and death; making an incision in the bitten anatomical region. It could be concluded that although blood incoagulability is associated with also early manifestations of botropic poisoning such as pain, edema, ecchymosis, systemic bleeding and shock, 'clinical evolution is not associated with the occurrence of blistering, necrosis, abscess, amputation, kidney failure and death, which occur later.